2019
DOI: 10.1038/s41598-019-44156-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Collagen Parameters in Pure Special Types of Invasive Breast Cancer

Abstract: One of the promising tools to evaluate collagen in the extracellular matrix is the second-harmonic generation microscopy (SHG). This approach may shed light on the biological behavior of cancers and their taxonomy, but has not yet been applied to characterize collagen fibers in cases diagnosed as invasive breast carcinoma (BC) of histological special types (IBC-ST). Tissue sections from 99 patients with IBC-ST and 21 of invasive breast carcinoma of no special type (IBC-NST) were submitted to evaluation of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
5
19
0
Order By: Relevance
“…[25][26][27] Furthermore, PPEF1 is involved in a variety of molecular functions related to tumor microenvironment, such as proteases, 28 platelet-derived growth factors and collagen. 29,30 Third, we have innovatively predicted the potential signaling pathways underlying the oncogenic activity of PPEF1 in BC by GSEA. The high expression of PPEF1 is mainly enriched in EMT, angiogenesis, TGF-β pathway, Focal adhesion and ECM receptor interaction (Figure 4, Table 3).…”
Section: Dovepressmentioning
confidence: 99%
“…[25][26][27] Furthermore, PPEF1 is involved in a variety of molecular functions related to tumor microenvironment, such as proteases, 28 platelet-derived growth factors and collagen. 29,30 Third, we have innovatively predicted the potential signaling pathways underlying the oncogenic activity of PPEF1 in BC by GSEA. The high expression of PPEF1 is mainly enriched in EMT, angiogenesis, TGF-β pathway, Focal adhesion and ECM receptor interaction (Figure 4, Table 3).…”
Section: Dovepressmentioning
confidence: 99%
“…Little is known about the involvement of CAFs in the biology of ILC, although one study has reported an increased CAF density in ILC compared to matched IDC samples [27], while differences in collagen deposition and alignment have also been reported [28,29]. Our analysis of primary CAFs from ILC and IDC shows differences in a number of genes involved in ECM interactions and signaling pathways, indicating that CAFs are able to differentially in uence the TME in ILC compared to IDC.…”
Section: Discussionmentioning
confidence: 66%
“…CAFs are an important component of the TME that regulate ECM deposition and secrete cytokines and growth factors to control metastatic spread and therapeutic response [26]. However, little is known about the involvement of CAFs in the biology of ILC, although one study has reported an increased CAF density in ILC compared to matched IDC samples [27], while differences in collagen deposition and alignment have also been reported in ILC [28,29]. Our analysis of primary CAFs from ILC and IDC shows differences in a number of genes involved in ECM interactions and signaling pathways indicating that CAFs are able to differentially influence the TME in ILC compared to IDC.…”
Section: Discussionmentioning
confidence: 99%